Anxiety symptoms in older Chinese adults in primary care settings: Prevalence and correlates - Xie, Qin; Xu, Yan-Min; Zhong, Bao-Liang (Frontiers in Public Health, 2022)
Background: Integrating mental health services into primary care is a potentially cost-effective way to decrease the treatment gap for anxiety in older adults but data on the epidemiology of anxiety symptoms in older Chinese adults in primary care settings have been very limited. This study investigated the prevalence and correlates of anxiety symptoms in Chinese older primary care patients. Methods: A total of 753 older primary care patients (≥65 years) were consecutively recruited from 13 primary care clinics in Wuhan, China, and interviewed with the validated Chinese version of the short form of the Geriatric Anxiety Inventory (GAI-SF). Results: The prevalence of anxiety symptoms (GAI-SF≥3) in older primary care patients was 21.1%. Statistically significant correlates of anxiety symptoms were female sex (vs. male, OR=1.85, P=0.002), poor economic status (vs. good, OR=2.31, P=0.013), fair and poor family relationship (vs. good, OR=1.85, P=0.006), hypertension (OR=2.01, P<0.001), chronic gastric ulcer (OR=6.82, P<0.001), and Parkinson's disease (OR=7.83, P=0.031). Conclusions: Anxiety symptoms are prevalent among older adults attending primary care clinics. Efforts for preventing or reducing anxiety symptoms in older primary care patients may be more useful to target those who are women, have poor financial status, don’t have a good family relationship, suffer from hypertension, have chronic gastric ulcer, and suffer from Parkinson's disease. e.